2020
DOI: 10.3390/jcm9124007
|View full text |Cite
|
Sign up to set email alerts
|

Portable Oxygen Therapy: Is the 6-Minute Walking Test Overestimating the Actual Oxygen Needs?

Abstract: The appropriate titration for the personalized oxygen needs of patients with chronic obstructive pulmonary disease (COPD) and severe hypoxemia is a determining factor in the success of long-term oxygen therapy. There are no standardized procedures to assist in determining the patient’s needs during the physical activities of daily life. Despite that effort tests are a wide broad approach, further research concerning the development of protocols to titrate O2 therapy is needed. The main objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Drawbacks of laboratory-based tests include the requirement for patient travel, the need for specialized equipment and environments, and/or the need for highly trained personnel. There is also some debate as to whether or not the current standard walk test (6-min-walk test) is a true test of endurance in ILD (103)(104)(105). In addition, most laboratory-based tests measure functional capacity, not functional performance, often making it difficult to translate results to day-to-day living.…”
Section: Functional Statusmentioning
confidence: 99%
“…Drawbacks of laboratory-based tests include the requirement for patient travel, the need for specialized equipment and environments, and/or the need for highly trained personnel. There is also some debate as to whether or not the current standard walk test (6-min-walk test) is a true test of endurance in ILD (103)(104)(105). In addition, most laboratory-based tests measure functional capacity, not functional performance, often making it difficult to translate results to day-to-day living.…”
Section: Functional Statusmentioning
confidence: 99%
“…There are studies simulating PADL in laboratory tests designed to measure oxygen desaturation 32 34 . For example, a recent publication comparing the 6MWT with a 20-min walking circuit 35 found that the 6MWT detected higher nadir SpO 2 and lower peak HR, but there were no results comparing activity intensity as energy expenditure between tests 35 . With SMARTREAB telemonitoring, our study further contributes with the findings that lower nadir SpO 2 and higher peak HR are detected in more intensive PADL compared to the 6MWT, such as walking, walking while carrying a weight, climbing stairs and doing household chores.…”
Section: Discussionmentioning
confidence: 99%
“…All the subjects answered a questionnaire at the end of the trial process assessing various features of oxygen therapeutic instruments. A portable prototype of oxygen concentration converter (PVSA) was introduced in order to simplify oxygen generation processes by adopting a deep evacuation phase in place of desorption by purge[27]. This study Journal of Thermal and Fluid Science www.rame.org.in includes experimental pulse volume, width and time delay measurements of the POC under three distinct conditions and two rest and activity related breathing rates [28].…”
mentioning
confidence: 99%